Case Report: Complications of an interscalene block with liposomal local anesthetic resulting in ICU admission for over 25 days—critical sequelae of outpatient surgical procedures - Byrne, Matthew C.; Anderson, Douglas H.; Meral, Ryan M. (Frontiers in Anesthesiology, 2025)
Interscalene blockade is a widely accepted regional analgesic technique that has been demonstrated to limit postoperative pain and opioid consumption in total shoulder arthroplasty. Phrenic nerve paresis is an unintended consequence of this block and is well-tolerated in the majority of patients. The development of liposomal bupivacaine (LB) offers the potential for extended-duration analgesia over standard bupivacaine. US Food and Drug Administration approval for the use of a specific preparation of LB for interscalene block was obtained in 2018, and research is ongoing on the analgesic duration, benefits, and side effect profile of this relatively new local anesthetic. We report on a case of a total shoulder replacement with a single-shot interscalene block with LB and subsequent intensive care unit admission for 25 days for persistent hypoxemia requiring bilevel positive airway pressure and heated high-flow oxygen. Following extensive evaluation by a multidisciplinary pulmonology and anesthesiology critical care team, it was determined that his hypoxemia was due to phrenic nerve palsy in the setting of interscalene nerve block in a patient with reduced pulmonary capacity at baseline, although no overt signs of severe or decompensated disease were identified preoperatively. Patient comorbidities, mechanisms to prolong blockade, and alternatives to an interscalene block should be carefully considered to avoid significant pulmonary complications.